Responsible communication strategies for small and medium-sized enterprises - Contreras Capella, Reynier Israel Ramírez Molina, Yanyn Aurora Rincón Quintero, Harold Bernardo Sukier, Jairo Antonio (Opción, 2019)
Organizational communication must respond to the demands of social responsibility and corporate sustainable development, establishing systemically productive interactions. The research aimed to propose responsible communication strategies for small and medium-sized enterprises. The study was projective, with a contemporary, transectional descriptive, documentary and virtual design. The findings show the importance of the management of organizational communication in small and medium enterprises, and the need to formulate a communication strategy articulated to social responsibility, for this reason, ECoRE-SME strategic guidelines are presented.